STRUCTURAL CHANGES VESSELS OF HEMOMICROCIRCULAR STREAM OF SUBMANDIBULAR GLAND OF RATS AFTER 1% EFFECTS OF METACYRIC ACID - Єрошенко, Г.А.; Крамаренко, Д.Р.; Solomchak, D.B.; Шевченко, К.В.; Вільхова, О.В.; Ячмінь, А.І. (World of Medicine and Biology, 2019)
Methyl methacrylate, as a material, is widely used for prosthetic beds, in the manufacture of orthodontic devices. In the scientific literature, there are numerous works devoted to the advantages and disadvantages of acrylic plastics, which are used to make removable denture bases. Morphological study of oral mucosal changes in the oral mucosa of the sexually mature white Wistar rats exposed to methyl methacrylate showed that with prolonged exposure to methyl methacrylate on the mucous membrane of the oral cavity, structural changes in all layers of the mucosa, forming the development of the toxic inflammatory process, are observed. There are degenerative changes in epithelial cells, signs of epithelium reparation, which is manifested by its hyperplasia, acanthosis and focal hyperkeratosis. In the submucosal layer, in some cases, signs of non-granulomatous inflammation are detected. Consequently, according to experts, during artificial teething using acrylic plastics it is necessary to take into account the possible toxic effect of methyl methacrylate and to take measures to reduce this effect. Under the influence of chronic intoxication with ethanol on the lobules of the submandibular gland in rats from the side of the metabolic link, the capillaries narrowing is observed, which is confirmed by a significant decrease in the outer diameter by 19.5% (p> 0.05) and the diameter of the lumen by 12.5% (p> 0.05 ), with a decrease in the thickness of the vascular wall by 30.4%. Since the ninth day there is a tendency towards the restoration of metric indices, but the normalization of indices till the final terms of the experiment is not determined. Thus, we observe the multi-directional reaction of the metabolic link vessels in the submandibular glands lobules to various exogenous stimuli: stable dilation in response to the action of 1% solution of methylether of methacrylic acid, but the changes are less sharp in nature, unlike small salivary glands of the palate, which are subjected to the direct influence of the stimulating agent, since they are located in the thickness of the oral cavity mucous membrane, and a sharp spasm is observed in the capillaries in the experimental model of chronic intoxication with ethanol, which has a faster (but short-term) and more aggressive action. In addition, changes under the action of methylmethacrylate are manifested as dilation of the vessels throughout the experiment, and under ethanol - as a tendency to parameters recovery, which is more likely to be explained by the properties of ethanol, as a metabolic substance, in contrast to methacrylate, which has a more toxic effect. Consequently, the vessels of the metabolic link of the submandibular salivary gland lobes in rats react with a stable dilation to the action of 1% solution of methacrylic acid methylether, which is confirmed by an increase in the diameter of the outer and the lumen diameter by 29.50% (p> 0.05) on the 14th day and by 17.99% (p> 0.05) on the 30th day of the experiment. Expansion of vascular lumen is also confirmed by the decrease of the Wagovert index by 31.44% compared to the control group. Recovery of the indices to the end of the experiment does not occur due to the constant toxic effect of the ether of methacrylic acid.